Analysis of Azerbaijan's 2024 Economy and Projections for 2025 - Gubad Ibadoghlu (ZBW - Leibniz Information Centre for Economics, 2024)
This article examines Azerbaijan's economic performance in 2024 and provides projections for 2025, highlighting key challenges and potential opportunities. Despite expectations for reform, 2024 was marked by persistent inflation, currency pressures, and declining investments, underscoring the enduring dominance of monopolistic practices and governance inefficiencies. Notable developments included rising prices for essential goods and services, a decrease in fixed capital investments, and heightened demand for foreign currency, leading to reduced reserves and capital outflows. Looking ahead to 2025, the economy is expected to face significant headwinds, including declining oil prices, inflationary pressures, and devaluation risks. These factors are projected to slow GDP growth, strain public finances, and exacerbate social inequality. Key initiatives, such as the "Azerbaijan 2030" strategic framework and the "Great Return" program, face implementation challenges, particularly amidst fiscal inefficiencies and limited transparency.
Keywords: 330; Azerbaijan; economy; GDP; oil and gas prices; inflation; devaluation; investments; monopolization; corruption; unfair competition